PENGARUH PULSING DENGAN AIR KELAPA DAN SUHU PENYIMPANAN TERHADAP MUTU BUNGA POTONG MAWAR (Rosa hybrida) - Riva R. Rengkuan; Ireine A.N. Longdong STP, MP; Dr. Ir. Lady C. Ch. Lengkey, MSi. (COCOS, 2017)
ABSTRACTEffects of pulsing and low temperature storage on the vase life of rose cut flowers had been studied. To prolong the postharvest life or flowering display of rose cut flowers by pulsing them after picking, that is, putting the stems in a sugar solution. The objectives of this study was to get the best pulsing time, vase life and quality change i.e the wilting percentage of rose cut flowers. First step of this research was pulsing the rose cut flowers with a coconut water for 1, 2, and 3 hours, then stored those flowers in low temperature 5,250C. The results showed that pulsing the rose cut flowers in coconut water for 2 hours is the best pulsing time and can prolong the vaselife until 40 days.Keyword : Pulsing, coconut water, rose cut flowers, cold storage